A challenging case of rheumatoid arthritis‐associated aortitis presenting with erythema nodosum after ST‐segment elevation myocardial infarction: A case report - Siripat Kaewnamchai; Bhakinai Temnithikul; Nopparat Ruchakorn; Teeranan Angkananard (Clinical Case Reports, 2022)
Abstract Rheumatoid arthritis is a systemic inflammatory disease that has many extra‐articular manifestations. Cardiovascular involvement, including coronary vasculitis and aortitis and skin lesion of erythema nodosum are uncommon findings of patients with rheumatoid arthritis, and thus, it is challenging for diagnosis of this case from those unusual extra‐articular presentation.